Factors that affects the dielectric properties of natural fibre reinforced hybrid biocomposite - Nishanthi Sunthrasakaran; Nor Akmal Mohd Jamail; Rahisham Abd. Rahman; Md Nor Ramdon Bin Baharom; Qamarul Ezani Kamarudin; Mohamad Farid Sies; W. Muhammad W. N. Azrina (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Almost all research on natural fibre reinforced composite has focused on the mechanical properties of the composite. Drawing on the important factors that effect the end product of composite, this paper reviews electrical properties of hybrid biocomposite when fibre content and surface treatment is varied. The compilation of dielectric constant, dissipation factor, loss factor and moisture absorption reported by researchers has been presented in this paper. The intrinsic characteristic of natural fibre which is hydrophilic is the main drawback that affects the electrical properties of the composite. Alkaline treatment on natural fibre has proven to overcome the hydrophilic characteristic and improves the adhesion between matrix and fibre. Besides that, the percentage of fibre content plays an important role in producing a good natural fibre reinforced hybrid composite. The moisture uptake, dielectric constant, dissipation factor and loss factor of the composite decreases with decreased fibre content.